Perancangan Sistem Pendukung Keputusan Berbasis Web Untuk Menentukan Asisten Laboratorium Komputer Menggunakan Algoritma Simple Additive Weighting - Rosma Siregar; Erita Astrid; Muhammad Dani Solihin (Bulletin of Computer Science Research, 2023)
The computer laboratory is one of the facilities that support the learning process, therefore, a professional laboratory management system is required to assist lecturers with computer laboratory upkeep. In the process of selecting laboratory assistants it takes quite a long time, is less efficient and cannot save the history of selection results automatically. So this research will create a decision support system using the simple additive weighting method to assist lecturers in selecting computer laboratory systems efficiently. The criteria used for selection were the GPA (Cumulative Achievement Index), Hardware Installation Tests, Software Installation Tests, LAN Installation Tests, Programming Tests, and Interviews. The final results of calculations using the simple additive weighting method will choose 2 alternatives with the highest scores to become computer laboratory assistants, namely alternative 4 (X4) with a value of 0.97 and alternative 2 with a value of 0.91 (X2). The decision support system will be built based on a website and the database system will use MySql.